Literasi Hukum Islam bagi Anak Yatim: Membangun Generasi Cerdas dan Bermartabat Melalui Kegiatan Bakti Sosial di Desa Hutaraja Lamo - Nur Hakimah Akhirani Nasution; Erwin Hamonangan; Yusniar Harahap; Helmi Suryana Siregar; Fitri Romaito Lubis (Yayasan Perguruan Kampus, 2025)
This community service project aims to enhance Islamic legal literacy among orphans in Hutaraja Lamo Village as an effort to shape an intelligent, ethical, and dignified generation. Orphans represent a vulnerable group that requires attention not only in material aspects but also in spiritual and educational development, including an understanding of their rights and responsibilities according to Islamic law. The activity was carried out in the form of a social service program, which included Islamic legal education, spiritual motivation, and the distribution of social assistance. The method used was an educational-participatory approach, consisting of preparation, implementation, and evaluation stages. The activity involved 35 orphaned children, religious leaders, and local community members. The materials delivered covered the rights of orphans in Islam, the importance of education, and the values of justice and social responsibility. The results of the program showed a significant improvement in the participants' basic understanding of Islamic law, along with more positive attitudes toward themselves and their environment. The impact of the activity includes educational, psychosocial, and sociocultural aspects, while also encouraging community participation in the ongoing development of orphans. This program made a meaningful contribution to the implementation of the Tri Dharma of Higher Education, particularly in the area of community service grounded in Islamic and humanitarian values. It is hoped that similar programs can be sustained and replicated to strengthen the role of Islamic law in nurturing a noble and capable young generation.